Does a loaded warm-up influence jump asymmetry and badminton-specific change of direction performance? - Yeung, W. V.; Bishop, C.; Turner, A. N.; Maloney, S. J. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Previously, it has been shown that loaded warm-up (LWU) can improve change-of-direction speed (CODS) in professional badminton players. However, the effect of asymmetry on CODS in badminton players and the influence of LWU on asymmetry has not been examined. Methods: A total of 21 amateur badminton players (age 29.5 [8.4] y, playing experience 8.4 [4.2] y) completed 2 trials. In the first, they performed a control warm-up. In the second, they performed the same warm-up but with 3 exercises loaded with a weight vest (LWU). Following both warm-ups, players completed single-leg countermovement jump and badminton-specific CODS tests. Results: No significant differences between control warm-up and LWU were observed for CODS, single-leg countermovement jump, or single-leg countermovement jump asymmetry. However, small effect sizes suggested faster CODS (mean difference: -5%; d = -0.32) and lower asymmetries (mean difference: -3%; d = -0.39) following LWU. Five players (24%) experienced CODS improvements greater than the minimum detectable change while 2 (10%) responded negatively. Asymmetry was not correlated with CODS following control warm-up (p = .079; P = .733) but was negatively associated with CODS after LWU (p = -.491; P = .035). Conclusion: LWU may prove a strategy to trial on an individual basis, but generic recommendations should not be applied.